1999
DOI: 10.1530/eje.0.1410637
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and retinoic acid induce the synthesis of insulin-like growth factor-binding protein-4 in prepubertal pig sertoli cells

Abstract: A large body of evidence suggests the existence of an intratesticular IGF system complete with ligands, receptors and binding proteins (IGFBPs); the aim of the present study was to evaluate tri-iodothyronine (T 3 ) and retinoic acid (RA) effects on IGFBP production by Sertoli cells. A significant dose-dependent increase in IGFBP-4 mRNA levels was observed in Sertoli cells cultured in the presence of physiological concentrations of T 3 or RA. This response was inhibited by cycloheximide, indicating that de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In this work, we have shown that hepatic IGFBP-4 expression is stimulated simultaneously by RA and T 3 , in agreement with data from other experimental models [38,39]. Both agents induce an increase in the IGFBP-4 mRNA content after several hours of incubation, and the effects are similar in magnitude.…”
Section: Discussionsupporting
confidence: 90%
“…In this work, we have shown that hepatic IGFBP-4 expression is stimulated simultaneously by RA and T 3 , in agreement with data from other experimental models [38,39]. Both agents induce an increase in the IGFBP-4 mRNA content after several hours of incubation, and the effects are similar in magnitude.…”
Section: Discussionsupporting
confidence: 90%
“…Early observations suggest that T3 regulates some of these paracrine factors. T3 stimulates Sertoli cell IGF-I secretion and IGFBP-4 mRNA expression [12,82]. It also stimulates serum immunoreactive inhibin-a levels and mRNA expression [8,100].…”
Section: Thyroid Hormones and Testicular Paracrine Factorsmentioning
confidence: 99%
“…Only half of the 20 genes were known to be expressed in Sertoli cells, i.e. c-jun, cyclin D2, GRP78 (Day and Lee 1989), IRF1 (Kanzaki and Morris 1998), proliferating cell nuclear antigen (PCNA; Schlatt and Weinbauer 1994), inhibin b A subunit (Kaipia et al 1992), IGFBP-3 (Smith et al 1990), IGFBP-4 ( Bardi et al 1999), cytokeratin-18 (Stosiek et al 1990) and Timp-2 (Grima et al 1996).…”
Section: Resultsmentioning
confidence: 99%